2016
DOI: 10.1007/s00211-016-0820-3
|View full text |Cite
|
Sign up to set email alerts
|

A non-symmetric coupling of the finite volume method and the boundary element method

Abstract: As model problem we consider the prototype for flow and transport of a concentration in porous media in an interior domain and couple it with a diffusion process in the corresponding unbounded exterior domain. To solve the problem we develop a new non-symmetric coupling between the vertex-centered finite volume and boundary element method. This discretization provides naturally conservation of local fluxes and with an upwind option also stability in the convection dominated case. We aim to provide a first rigo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…For the analysis of the system (28) we employ some results from the stationary FVM-BEM coupling [EOS17]. The main idea is to measure the discrete difference between the right-hand sides and the bilinear forms (10) and (26):…”
Section: Semi-discretizationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis of the system (28) we employ some results from the stationary FVM-BEM coupling [EOS17]. The main idea is to measure the discrete difference between the right-hand sides and the bilinear forms (10) and (26):…”
Section: Semi-discretizationmentioning
confidence: 99%
“…Remark 15. The restriction b·n ∈ P 0 (E in Γ ) in [EOS17,Lemma 7], where E in Γ denotes the set of all edges on the inflow boundary Γ in , results from the estimate [EOS17, Lemma 6]. However, this is not necessary.…”
Section: Semi-discretizationmentioning
confidence: 99%
See 1 more Smart Citation
“…• Based on an argument of Sayas [Say09], Steinbach [Ste11] showed that the nonsymmetric coupling of the elliptic-elliptic interface problem with a lowest order term in the interior domain in fact leads to a coercive variational formulation; see also [EOS17]. This allows us to extend the results of [MS87,CES90] to the non-symmetric coupling method on non-smooth domains.…”
Section: Introductionmentioning
confidence: 97%
“…We can also interpret the model that the (unbounded) exterior problem "replaces" the (unknown) boundary conditions of the interior problem [Era12, Remark 2.1]. Recently, the non-symmetric vertex-centered FVM-BEM coupling approach was introduced in [EOS15], which results in a smaller system of linear equations than the previous three field coupling approach cited above. However, a posteriori estimators for this kind of FVM-BEM coupling were not developed.…”
Section: Introduction and Model Problemmentioning
confidence: 99%